2022
DOI: 10.3390/nano12101771
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Unsteady Hybrid Nanofluid Flow over the Falkner-Skan Wedge

Abstract: Numerous manufacturing processes, including the drawing of plastic films, have a major impact on mass transport. These functionalities necessitate the solution of the Falkner–Skan equation and some of its configurations when applied to various geometries and boundary conditions. Hence, the current paper discusses the impact of unsteady hybrid nanofluid flow on a moving Falkner–Skan wedge with a convective boundary condition. This problem is modeled by partial differential equations, which are then converted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The hybrid nanofluid flow subjected to the unsteadiness decelarating case was analyzed by Zainal et al. [32–36] for various geometries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hybrid nanofluid flow subjected to the unsteadiness decelarating case was analyzed by Zainal et al. [32–36] for various geometries.…”
Section: Introductionmentioning
confidence: 99%
“…The discussions regarding the thermal and flow characteristics of hybrid nanofluids were reported by Khashi'ie et al [21][22][23][24] for disc case, Khan et al [25][26][27] for wedge and cylinder geometries and Lund et al [28][29][30][31] for stretching/shrinking plate. The hybrid nanofluid flow subjected to the unsteadiness decelarating case was analyzed by Zainal et al [32][33][34][35][36] for various geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, due to the rise of nanofluid research, it has prompted researchers to merge this state-of-the-art working fluid to jet impingement cooling to replace the conventional working fluid. Such implementation resulted in positive effects where the heat transfer performance improved remarkably, reducing the weight and size of the jet impingement design, which led to lower capital cost in fabricating the cooling system [16,18]. Heat transfer enhancement in jet impingement cooling with CuO/water nanofluid was experimentally performed by Modak et al [19], who concluded with three reasons why the presence of nanofluid in jet impingement improved the heat transfer rate.…”
Section: Introductionmentioning
confidence: 99%